Lipid peroxidation: the role or Ca2+ and protection by calcinine - Pereira, R. S. [UNESP] (Medecine Et Hygiene, 1996)
When calcinine (A-23187) (2 mu M), a known Ca2+ ionophore, is present, a significant protection is observed to a mitochondrial suspension undergoing lipid peroxidation by Fe2+-citrate complex. A-23187 can remove Ca2+, which seems to have an important role in the lipid peroxidation process, from its 'lesive sites' and consequently preventing the damage. This information has importance in terms of knowing the mechanisms and avoiding the damages of lipid peroxidation that occur in some pathological cases such as tumor promotion and hemochromatosis.
Keywords: A-23187; Ca2+; Lipid peroxidation; Mitochondria; Calcimycin; Calcium ion; Ferric citrate; Animal tissue; Controlled study; Hemochromatosis; Lipid peroxidation; Mitochondrion; Nonhuman; Rat; Tumor promotion; Animals; Calcimycin; Calcium; Ionophores; Lipid Peroxidation; Membrane Potentials; Mitochondria, Liver; Rats; Rats, Wistar; Reactive Oxygen Species